2003
DOI: 10.1002/ajh.10413
|View full text |Cite
|
Sign up to set email alerts
|

Refractory autoimmune thrombocytopenic purpura: Responses to treatment with a recombinant antibody to lymphocyte membrane antigen CD20 (rituximab)

Abstract: ''Refractory'' autoimmune thrombocytopenia represents a life-threatening condition, having failed to respond to a variety of therapeutic measures. We report a series of cases, all failing splenectomy and multiple therapeutic programs, including, in two patients, marrow transplant. Five of the six cases reported responded to a recombinant antibody to the lymphocyte membrane antigen CD20 (rituximab), an agent commonly employed in the treatment of non-Hodgkin's lymphoma. Our experiences over a period of 4 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Most patients will sustain a hemostatic response after splenectomy, although relapses can occur at any time [8] . Refractory idiopathic thrombocytopenic purpura represents a life-threatening condition that fails to respond to a variety of therapeutic measures [9] . In recent years, immunosuppressive agents such as cyclosporine A and MMF were used to treat refractory ITP as second line drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients will sustain a hemostatic response after splenectomy, although relapses can occur at any time [8] . Refractory idiopathic thrombocytopenic purpura represents a life-threatening condition that fails to respond to a variety of therapeutic measures [9] . In recent years, immunosuppressive agents such as cyclosporine A and MMF were used to treat refractory ITP as second line drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects were found to be better in male patients than female patients. 9 /L) over 6 months, unrelated to any underlying viral infection, collagen vascular diseases, malignancy, or medications; (2) without or with slight splenomegaly, with a normal or increased number of megakaryocytes in bone marrow, and no failure of maturing; (3) the failure of drug treatment and surgery treatment (prednisone, vincristine, danazol, long-term use of traditional Chinese medicine or intravenous injection of high doses of immunoglobulin G and splenectomy) ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Rituximab, a chimeric anti-CD20 monoclonal antibody, causes a rapid depletion of B cells [9]. Although rituximab was originally introduced for the treatment of malignant lymphomas [10,11], several recent studies have shown that rituximab may also be effective in the treatment of ITP and other autoimmune diseases [12,19,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The current results of all published case reports and clinical trials using rituximab in the treatment of immune thrombocytopenias have most recently been reported showing an overall response rate of about 50% [34].…”
Section: Introductionmentioning
confidence: 99%
“…PAIg levels, however, did not correspond to platelet count responses in three of the patients studied [20]. Although pretreatment levels of PAIgG antibodies were significantly increased in six of these patients, only one of the responders displayed a posttreatment decline in these autoantibody levels [107].…”
Section: Laboratory Resultsmentioning
confidence: 99%
“…Different targeted immunotherapies have been explored in chronic refractory ITP, such as anti-CD20, anti-CD154 and anti-CD52 antibodies [19][20][21]. This review will summarize the therapeutic mechanisms and clinical results of rituximab, a chimeric anti-CD20 monoclonal antibody, in the treatment of chronic ITP.…”
Section: Introductionmentioning
confidence: 99%